2005
DOI: 10.1128/aac.49.2.518-524.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Import by Aspergillus fumigatus and Its Influence on Antifungal Potency of Sterol Biosynthesis Inhibitors

Abstract: High mortality rates from invasive aspergillosis in immunocompromised patients are prompting research toward improved antifungal therapy and better understanding of fungal physiology. Herein we show that Aspergillus fumigatus, the major pathogen in aspergillosis, imports exogenous cholesterol under aerobic conditions and thus compromises the antifungal potency of sterol biosynthesis inhibitors. Adding serum to RPMI medium led to enhanced growth of A. fumigatus and extensive import of cholesterol, most of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 56 publications
0
38
2
Order By: Relevance
“…In a related study on cholesterol import by Aspergillus fumigatus and its influence on the antifungal potency of ergosterol biosynthesis inhibitors, specifically 14a-demethylase inhibitors, it was concluded that adding serum or cholesterol to the medium partially rescues fungal cells from the drug-induced growth inhibition (33), a finding that is contrary to the observations described here with TB. However, the possibility that cholesterol can serve as an ergosterol surrogate for the cell membrane is entirely consistent with our view (29) and that of others (30)(31)(32) that distinct sterol structures are involved with multiple functions.…”
Section: Discussioncontrasting
confidence: 56%
“…In a related study on cholesterol import by Aspergillus fumigatus and its influence on the antifungal potency of ergosterol biosynthesis inhibitors, specifically 14a-demethylase inhibitors, it was concluded that adding serum or cholesterol to the medium partially rescues fungal cells from the drug-induced growth inhibition (33), a finding that is contrary to the observations described here with TB. However, the possibility that cholesterol can serve as an ergosterol surrogate for the cell membrane is entirely consistent with our view (29) and that of others (30)(31)(32) that distinct sterol structures are involved with multiple functions.…”
Section: Discussioncontrasting
confidence: 56%
“…However, be- (19,20). Another effect of serum on Aspergillus growth is the exogenous import of human cholesterol by A. fumigatus, providing a substitute for fungal membrane ergosterol (27). This effect may contribute to the decreased antifungal activity of amphotericin B in the presence of serum found in the present study, since cholesterol has a lower affinity for amphotericin B (28).…”
Section: Discussioncontrasting
confidence: 41%
“…It has been proposed that aerobic uptake of exogenous sterol (e.g., host cholesterol) contributes to azole (1,26) and polyene (12) resistance in vivo, and a putative sterol transporter gene for C. glabrata (AUS1) has been identified (26). The genetic controls and biological consequences of obligate and facultative sterol uptake in C. glabrata require further investigation, not least because the potential exists for similarities with other opportunistic pathogens, such as Aspergillus fumigatus (41) and Pneumocystis jirovecii (14).…”
mentioning
confidence: 99%